2014
DOI: 10.1128/jb.02202-14
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Dependent Control of Respiratory Nitrate Reduction in Mycelium of Streptomyces coelicolor A3(2)

Abstract: Several members of the obligately aerobic genus Streptomyces are able to reduce nitrate, catalyzed by Nar-type respiratory nitrate reductases. A unique feature of Streptomyces coelicolor A3(2) compared with other streptomycetes is that it synthesizes three nonredundant Nar enzymes. In this study, we show that Nar2 is the main Nar enzyme active in mycelium and could characterize the conditions governing its synthesis. Nar2 was present at low levels in aerobically cultivated mycelium, but synthesis was induced w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 42 publications
2
31
1
Order By: Relevance
“…The transcriptomics and proteomics data in the study suggested that N. eutropha strain C91 tuned down the assimilatory metabolism while retaining or stimulating dissimilatory metabolism upon anoxic incubation with NO 2 as the surrogate oxidant. A Grampositive obligate aerobic bacterium, Streptomyces coelicolor A3(2), was also found to utilize its Nar-type respiratory nitrate reductase to survive extended periods of anoxia, although no growth was observed in the absence of O 2 (36,37). The utilization of N 2 O as a temporary substitute for O 2 in G. aurantiaca strain T-27 may be another such lifestyle that strictly aerobic microorganisms have adopted to generate cell maintenance energy to survive through periods of anoxia.…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptomics and proteomics data in the study suggested that N. eutropha strain C91 tuned down the assimilatory metabolism while retaining or stimulating dissimilatory metabolism upon anoxic incubation with NO 2 as the surrogate oxidant. A Grampositive obligate aerobic bacterium, Streptomyces coelicolor A3(2), was also found to utilize its Nar-type respiratory nitrate reductase to survive extended periods of anoxia, although no growth was observed in the absence of O 2 (36,37). The utilization of N 2 O as a temporary substitute for O 2 in G. aurantiaca strain T-27 may be another such lifestyle that strictly aerobic microorganisms have adopted to generate cell maintenance energy to survive through periods of anoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Growth of S. coelicolor A3(2) strains as highly dispersed liquid cultures in Duran-F tubes with MOPS-buffered TSB was performed as described [Fischer et al, 2014]. Standardized 15-h exponential cultures (20 mL) were inoculated with 2 mL of a standard mycelium suspension.…”
Section: Bacterial Strains and Culture Conditionsmentioning
confidence: 99%
“…The inorganic nitrogen cycling results provide important information regarding the transition from aerobic to anaerobic conditions as the water level declines. The competing requirements of nitrate respiration, which necessitates oxygen-limiting conditions at a minimum (61), and NO dioxygenase needing molecular oxygen, collectively suggest that at day 4 the trench waters were no longer aerobic, but more likely microaerophilic/hypoxic. However, many facultative anaerobes are capable of using nitrate as an alternate electron acceptor when oxygen is not available.…”
Section: Resultsmentioning
confidence: 99%